INTERNATIONAL COMMUNITY SERVICE THROUGH AZAIB HOLDINGS' DEVELOPMENT STRATEGY IN PREMIUM CHOCOLATE INDUSTRY IN KUALA LUMPUR, MALAYSIA - Nawir, Jubaedah; Yulivan, Ivan; Hadi, Abdul Razak Abdul; Saragih, Guntur Syahputra; Putriningtyas, Indira; Dedari, Sintha Yulia; Supriadi, Yudi Nur (Yayasan Education and Social Center, 2024)
The International Community Service Team between UPN Veteran Jakarta Lecturers and Students in Kuala Lumpur chose Azaib Holdings Sdn Bhd as a partner in implementing a community service program, which aims to empower the community through a premium chocolate company development strategy. Azaib Holdings, a Malaysian SME focused on healthy and high-quality chocolate products, faced funding constraints but sought to increase production capacity to face competition in the premium chocolate market. This program uses the method of direct visits to production sites at Mara Refinery (KIMAR), interviews with management, and operational observations to provide solutions in improving efficiency and resource utilization. The results show that with the merger of Azaib Holdings with KIMAR, the company has succeeded in reducing operational costs related to facility maintenance and waste management, which is now the responsibility of KIMAR. The program also contributes to upskilling local communities, strengthening their role in the chocolate industry, opening up new job opportunities, and increasing the competitiveness of local products in the international market